DETERMINING YOUTH CHOICE OF ENTERPRISE IN AQUACULTURE PRODUCTION FOR JOB CREATION IN ABIA STATE, NIGERIA - IFEJIKA, P.I; ASADU, A.N; ENWELU, I.A; SANNI, A.O; NWABEZE, G.O; OMEJE, J. (Nigerian Journal of Fisheries, 2015)
Aquaculture production provides an entry point to create jobs for youth which prompted the study to determine their choice of enterprise in aquaculture production across gender in Abia State. Interview schedule was used to elicit information from 171 randomly selected respondents in six local government areas which was analysed with cross tabulation along gender and t-test. The result affirmed that aquaculture met youth inspiration on economic drive as prime motive to seek for job and be independent. Both genders were attracted to aquaculture production enterprise for monetary purpose rather than food and pleasure. Interestingly, youths indicated more interest in rearing of table size fish production enterprise than fingerling and brood-stock enterprises. Also, youths got to know about aquaculture through eight information mediums mostly through mobile phone, television and friends. Result of t-test established that significant difference exists between the men and women gender as calculated t-ratio (2.18) was greater than the t-critical (.160). It indicates that men made better choices than women on motivation, information sources and on choice of enterprise in aquaculture production. Based on the finding, communication strategy for youth sensitization and promotion on aquaculture production enterprises should consider mobile phone in combination with other mass media, interpersonal and group methods. Meanwhile, emphasis should be placed on table size aquaculture production enterprise that most youths showed curiosity. Therefore, concerted effort should be directed towards promotion and empowerment of desiring youths with capacity building and credit facilities to realise the dream in aquaculture production enterprise for job creation.